Negative psychological responses of injury and rehabilitation adherence effects on return to play in competitive athletes: a systematic review and meta-analysis - Ivarsson, A.; Tranaeus, U.; Johnson, U.; Stenling, A. (Open Access Journal of Sports Medicine, 2017)
Previous research offers evidence that psychological factors influence an injured athlete during the rehabilitation process. Our first objective was to conduct a systematic review and meta-analysis of the results from all published studies that examined the relationships among negative affective responses after sport injuries, rehabilitation adherence, and return to play (RTP). The second objective was to use a meta-analytic path analysis to investigate whether an indirect effect existed between negative affective responses and RTP through rehabilitation adherence. This literature review resulted in seven studies providing 14 effect sizes. The results from the meta-analysis showed that negative affective responses had a negative effect on successful RTP, whereas rehabilitation adherence had a positive effect on RTP. The results from the meta-analytic path analysis showed a weak and nonsignificant indirect effect of negative affective responses on RTP via rehabilitation adherence. These results underline the importance of providing supportive environments for injured athletes to increase the chances of successful RTP via a decrease in negative affective responses and increase in rehabilitation adherence.